DBD plasma treatment and chitosan layers - A green method for stabilization of silver nanoparticles on polyamide 6.6 - Ribeiro, Ana Isabel Ferreira (2020)
The addition of silver nanoparticles (AgNPs) to biomedical textiles can be of great interest to protect the materials against microorganisms and prevent their spread. However, the human and environmental over‐exposure to AgNPs is leading to numerous concerns due to their toxicity. In this work, AgNPs were stabilized onto polyamide 6.6 fabrics (PA66) through atmospheric dielectric barrier discharge (DBD) plasma treatment and the use of chitosan (Ch) layers applied by spray. DBD plasma treatment revealed a crucial role in AgNPs adhesion (4.8 and 6.3 At%). A first layer of Ch decreased the AgNPs adhesion in both untreated and DBD plasma‐treated samples but treated samples show higher concentration (1.7 and 4.1 At%). The antibacterial activity was evaluated against Staphylococcus aureus and Escherichia coli after 2 and 24 h, showing a superior action in all samples with DBD plasma treatment after 24 h. The Ch in the first layers of the composites delayed the antimicrobial action of the samples but it also may enhance antimicrobial action. The obtained coatings will allow the development of novel and safe wound dressings with improved AgNPs deposition, controlled ions released and consequently, manage the antimicrobial performance and minimize the AgNPs side effects.